2019
DOI: 10.3390/biomimetics4020042
|View full text |Cite
|
Sign up to set email alerts
|

Cupric Oxide Nanostructures from Plasma Surface Modification of Copper

Abstract: Taking inspiration from the hydrophilic and superhydrophilic properties observed from the nanostructures present on the leaves of plants such as Alocasia odora, Calathea zebrina, and Ruelia devosiana, we were able to synthesize cupric oxide (CuO) nanostructures from the plasma surface modification of copper (Cu) that exhibits hydrophilic and superhydrophilic properties. The Cu sheets were exposed to oxygen plasma produced from the P300 plasma device (Alliance Concept, Cran-Gevrier, France) at varying power, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
1
6
0
1
Order By: Relevance
“…This may be attributed to the increase in interaction of the different plasma species with the samples which lead to the increase in surface roughness that simultaneously occurs as the oxide layer is formed. This is corroborated by the findings of [69] where they found that at high irradiation power and duty cycle, plasma treatment resulted to physical and chemical change on the material. After, all the samples became superhydrophobic, with θ ranging from 150° to 160°, Table 1.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…This may be attributed to the increase in interaction of the different plasma species with the samples which lead to the increase in surface roughness that simultaneously occurs as the oxide layer is formed. This is corroborated by the findings of [69] where they found that at high irradiation power and duty cycle, plasma treatment resulted to physical and chemical change on the material. After, all the samples became superhydrophobic, with θ ranging from 150° to 160°, Table 1.…”
Section: Resultssupporting
confidence: 65%
“…Irradiation power was varied from 300 W to 600 W at a fixed irradiation time of 10 minutes. Additional details of the plasma device may be found in [69]. Formation of self‐assembled monolayers (SAM) is achieved by immersing the plasma treated samples in a 2.5 mM solution of n‐octadecyl mercaptan (Sigma Aldrich) in ethanol for 15 h. The samples were then washed with ethanol and allowed to dry in air.…”
Section: Materials and Experimental Detailsmentioning
confidence: 99%
“…The main content of copper oxide generated in low-power oxygen plasma is Cu 2 O, which is related to the low activation energy required for the formation of Cu 2 O [32]. Therefore, the theoretical models of the fs-laser interaction with Cu and Cu 2 O were established to simulate the ablation of samples by a single-pulse fs-laser with different laser fluences.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The textile samples were irradiated using oxygen plasma produced from a P300 plasma device (Alliance Concept, France). The schematic diagram and the complete details of the device is described in [52]. The vacuum chamber was first evacuated using a 20 m 3 /h rotary pump and the base pressure was achieved at 6.0 x 10 -2 mbar.…”
Section: Plasma Parametersmentioning
confidence: 99%